2009
DOI: 10.1093/petrology/egp084
|View full text |Cite
|
Sign up to set email alerts
|

Highly Refractory Peridotites on Macquarie Island and the Case for Anciently Depleted Domains in the Earth’s Mantle

Abstract: Macquarie Island (Southern Ocean) is a fragment of Miocene ocean crust and upper mantle formed at a slow-spreading ridge system, uplifted and currently exposed above sea-level. The crustal rocks on the island have unusually enriched compositions and the strong signature of an enriched source requires low overall degrees of melt depletion in the underlying mantle. Peridotites on the island, however, are highly refractory harzburgites that can be modeled as residues of420^25% of near-fractional melting from whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(27 citation statements)
references
References 77 publications
3
24
0
Order By: Relevance
“…This scenario is consistent with Os data indicating ages > 1 billion years for abyssal peridotites (Alard et al, 2005;Brandon et al, 2000;Harvey et al, 2006;Liu et al, 2008) and Hf isotopes pointing to extreme and ancient mantle depletion in the oceanic mantle (Stracke et al, 2011). The role and importance in volume of anciently depleted refractory mantle might have been overlooked until now because of its 'sterility' (Dijkstra et al, 2010).…”
Section: The St Peter's and St Paul's Islands In The Atlanticsupporting
confidence: 83%
See 2 more Smart Citations
“…This scenario is consistent with Os data indicating ages > 1 billion years for abyssal peridotites (Alard et al, 2005;Brandon et al, 2000;Harvey et al, 2006;Liu et al, 2008) and Hf isotopes pointing to extreme and ancient mantle depletion in the oceanic mantle (Stracke et al, 2011). The role and importance in volume of anciently depleted refractory mantle might have been overlooked until now because of its 'sterility' (Dijkstra et al, 2010).…”
Section: The St Peter's and St Paul's Islands In The Atlanticsupporting
confidence: 83%
“…Harzburgites in Macquarie Island, southwest Pacific, occur at the base of a complete section of exhumed oceanic crust. Hence, the Macquarie section is commonly considered as an ophiolite, although it was not obducted (Dijkstra and Cawood, 2004;Dijkstra et al, 2010;Goscombe and Everard, 2001;Varne, 1978, 1980;Varne et al, 1969).…”
Section: Oceanic Peridotitesmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the clearest and freshest domains of pyroxene grains were selected, submicron sized cracks and alteration veinlets following the crystallographic directions could not be avoided. In agreement with Dijkstra et al [2010], anomalously high counts of Pb, U, Ba, and to a lesser extent Sr, are attributed to microheterogeneities. Opx is particularly sensitive to alteration effects due to its extremely low trace element content and to the fact that it is more alterable than Cpx.…”
Section: Methodssupporting
confidence: 72%
“…Den Tex, 1969;Wyllie, 1969), including the Lherz peridotite, has been the subject of much debate and it has been suggested that these layered assemblages of peridotite and pyroxenite may represent; (1) exhumed sub-continental lithospheric mantle (e.g., Menzies and Dupuy, 1991;Reisberg and Lorand, 1995;Burnham et al, 1998;Downes, 2001) from the mechanical boundary layer (MBL; White, 1988), or (2) inherited heterogeneities from asthenospheric upper-mantle (c.f. Peate et al, 1997;Parkinson and Pearce, 1998;Brandon et al, 2000;Bizimis et al, 2005;Harvey et al, 2006;Mü ntener and Manatschal, 2006;Bizimis et al, 2007;Liu et al, 2008;Simon et al, 2008;Liu et al, 2009;Warren et al, 2009;Dijkstra et al, 2010;Ishikawa et al, 2011 for examples of isotopic and mineralogical heterogeneity present in Earth's upper-mantle) that may even be linked to upwelling diapirs (e.g., Bodinier et al, 1988;Fabriès et al, 1991). Several authors have used the chemistry of mantle materials to provide estimates of the composition of primitive upper mantle (PUM) and bulk-silicate Earth (BSE; e.g., Palme and Nickel, 1985;Zindler and Hart, 1986;McDonough and Sun, 1995;Becker et al, 2006), and some authors have integrated information from ultramafic bodies into models of the spatial distribution of chemical diversity in Earth's upper mantle (e.g., Allègre and Turcotte, 1986;Morgan and Morgan, 1999).…”
Section: Introductionmentioning
confidence: 99%